SUV39H1 downregulation induces deheterochromatinization of satellite regions and senescence after exposure to ionizing radiation - Sidler, Corinne; Li, Dongping; Wang, Bo; Kovalchuk, Igor; Kovalchuk, Olga (Frontiers in Genetics, 2014)
While the majority of cancer patients are exposed to ionizing radiation during diagnostic and therapeutic procedures, age-dependent differences in radiation sensitivity are not yet well understood. Radiation sensitivity is characterized by the appearance of side effects to radiation therapy, such as secondary malignancies, developmental deficits, and compromised immune function. However, the knowledge of the molecular mechanisms that trigger these side effects is incomplete. Here we used an in vitro system and showed that low-senescent normal human diploid fibroblasts (WI-38) senesce in response to 5 Gy IR, while highly senescent cultures do not show changes in cell cycle regulation and only a slight increase in the percentage of senescent cells. Our study shows that this is associated with changes in the expression of genes responsible for cell cycle progression, apoptosis, DNA repair, and aging, as well as transcriptional and epigenetic regulators. Furthermore, we propose a role of the downregulation of SUV39H1 expression, a histone methyltransferase that specifically trimethylates H3K9, and the corresponding reduction in H3K9me3 levels in the establishment of IR-induced senescence.